Normal lymphatic development and function in mice deficient for the lymphatic hyaluronan receptor LYVE-1. - Gale, N; Prevo, R; Espinosa, J; Ferguson, D; Dominguez, MG; Yancopoulos, G; Thurston, G; Jackson, D (2007)
The hyaluronan receptor LYVE-1 is expressed abundantly on the surfaces of lymphatic vessels and lymph node sinus endothelial cells from early development, where it has been suggested to function both in cell adhesion/transmigration and as a scavenger for hyaluronan turnover. To investigate the physiological role(s) of LYVE-1, we generated mice in which the gene for the receptor was inactivated by replacement with a beta-galactosidase reporter. LYVE-1(-/-) mice displayed an apparently normal phenotype, with no obvious alteration in lymphatic vessel ultrastructure or function and no apparent change in secondary lymphoid tissue structure or cellularity. In addition, the levels of hyaluronan in tissue and blood were unchanged. LYVE-1(-/-) mice also displayed normal trafficking of cutaneous CD11c(+) dendritic cells to draining lymph nodes via afferent lymphatics and normal resolution of oxazolone-induced skin inflammation. Finally, LYVE-1(-/-) mice supported normal growth of transplanted B16F10 melanomas and Lewis lung carcinomas. These results indicate that LYVE-1 is not obligatory for normal lymphatic development and function and suggest either the existence of compensatory receptors or a role more specific than that previously envisaged.